Hepatitis B Virus Reactivation Following Treatment of HNSCC With Cisplatin. (April 2022) - Crosby, James; Smith, Forrest; Ganti, Subramanya Shyam; Moka, Nagabhishek; Bailey, Samuel
Hepatitis B Virus (HBV) reactivation is a known complication of intense immunosuppression with B-cell depleting monoclonal antibody therapy and transplantation immunosuppression. HBV reactivation has occurred following treatment with chemotherapy regimens for hematologic malignancies and solid tumors. There are 2 prior case reports of HBV reactivation following cisplatin monotherapy for head and neck squamous cell carcinoma (HNSCC). Here, we present a case of a 49-year-old Caucasian male with a past medical history of laryngeal squamous cell carcinoma (SCC). There are no consensus guidelines on how to define hepatitis B reactivation. There are guidelines on when to initiate prophylaxis with Entecavir while on immunosuppressive therapy with risk according to medication category and hepatitis B surface antigen/hepatitis B core antibody IgG serology. CDC recommends screening everyone. American Society of Clinical Oncology (ASCO) now with a recent update in 2020 recommends screening everyone. There is a definite role of immunosuppression in HBV reactivation, however, there is also direct enhancement by cisplatin of viral replication by creating endoplasmic reticulum stress which increases HBV DNA indirectly. Finally, cytotoxicity enhances HBV reactivation and immune reconstitution post withdrawing immunosuppressive treatment. Because of the effects of chemotherapy, aka cisplatin goes beyond immunosuppression-related reactivation of HBV, our recommendations are in line with CDC and ASCO to screen all patients for HBV before onset of chemotherapy and start Entecavir/Tenofovir Disoproxil Fumarate before the onset of chemotherapy for HBV-positive patients.